Association of Face Mask Use With Nasal Symptoms And Mucociliary Clearance - Akbal ÇufalI, Şeyda; Arslan, Dilay; Faruk Çufalı, Ömer; Rıza Yağmur, Ali; Murat Özcan, Kürşat; Çolak, Mustafa (ENT Updates, 2023)
Background: Masks may have negative impacts on health; thus, it is important to investigate mask-related symptoms and the effects of masks on mucociliary clearance. We conducted our investigation using 4 study groups to determine the longterm health effects of both surgical and respiratory masks. Methods: We studied 139 people aged 18-65 years. Participants were divided into 4 groups: single surgical mask, double surgical mask, N95 or equivalent mask alone, and surgical mask in combination with N95 or equivalent mask. The saccharin test was used to measure the mucociliary clearance times. We performed the saccharin test with a 1 × 1 × 1 mm piece of saccharin (Hermesetas®) and sterile-appropriate technique. Results: In this study, no significant difference was found between the groups in terms of saccharin transition time. Prolongation of mask wearing time was positively correlated with headache symptom, with the correlation coefficient of 0.26 (P=.002). It was also found that not wearing an N95 mask reduced the symptom of earache 0.35 times (P=.025). Conclusion: In this study, no severe symptoms were detected that would limit the use of masks. It was demonstrated by the saccharin test that the use of masks did not affect nasal physiology.